Diagnostic and Prognostic Significance of miR-675-3p in Patients With Atherosclerosis - Wang, Shuangquan (Clin Appl Thromb Hemost, 2021)
In recent years, a rising number of studies have confirmed that microRNA (miRNA) plays a prominent role in the early diagnosis and prognostic value assessment of cardiovascular diseases. The current study was conducted to examine the expression of miR-675-3p in atherosclerosis (AS) patients and to evaluate its clinical diagnosis and prognostic value. 110 AS patients and 70 healthy controls were included in the study. Serum miR-675-3p levels were detected by quantitative real-time PCR (qRT-PCR). The clinical diagnostic significance of serum miR-675-3p in AS patients were investigated by the receiver operating characteristic (ROC) curve. The correlation between miRNA and carotid intima-media thickness (CIMT) was analyzed by the Spearman correlation coefficient. The prognostic significance of serum miR-675-3p was evaluated by the Kaplan-Meier method and Cox regression analysis. The patient’s serum miR-675-3p was significantly increased than the healthy individuals (P < 0.05). An increase of carotid intima-media thickness (CIMT) was positively correlated with the promotion of serum miR-675-3p levels. The area under the ROC curve (AUC) was 0.918, with high sensitivity and specificity. miR-675-3p is a key independent predictor of cardiovascular adverse events in AS patients (HR = 5.375, 95%CI = 1.590-18.170, P = 0.007), and patients with elevated miR-675-3p were more likely to have cardiovascular adverse events (log-rank P = 0.030). Increased miR-675-3p can be used as a potential marker for the diagnosis of AS, and was associated with the poor prognosis of AS.